Legal Reform in Legal Responsibility for the Use of Public Roads for the Transportation of Mining Products (Case Study of Transportation of Mining Products in West Aceh Regency) - Kurdi, Kurdi; Syafitri, Cut Zulfahnur (JURNAL MERCATORIA, 2024)
Transportation plays an important role in supporting economic growth and regional connectivity, but the use of public roads for hauling activities by mining companies in West Aceh Regency has caused significant problems such as road damage, pollution, and accident risk. This condition is exacerbated by a legal vacuum at the local level that does not specifically regulate the use of public roads for the transportation of mining products, although national regulations such as the Mineral and Mineral Law and regulations related to reclamation already exist. This study uses normative juridical methods with legislative and conceptual approaches to analyze applicable legal provisions and identify legal gaps, as well as formulate legal reform solutions. The results of the study show the need for the preparation of clear regional regulations (Qanun), including the setting of operational schedules, quota systems, and real-time monitoring. In addition, the government's cooperation with business entities (PPP) to build special hauling roads through the DBOMFT scheme is proposed as a constructive solution to reduce the burden on public roads and increase regional revenue. Legal reform at the regional level is expected to provide legal certainty, protect the community, and minimize negative impacts on the environment and infrastructure.